Pengembangan Kakas Bantu Pemeriksa Kesalahan pada Skenario Use Case dalam Bahasa Indonesia - Muhammad Alimuddien Rasyid; Denny Sagita Rusdianto; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In general, use case scenario reviewing is done manually, which has two drawbacks. The first drawback is the reviewing process takes a long time to finish, and the second drawback is the high level of dependence on reviewer's ability. Therefore, manual reviewing can lead into inconsistent scenario assessment. An automatic use case scenario review mechanism have existed before, but this mechanism was designed according to English which has some differences with Indonesian within the sentence's structure. There are some challenges to develop a use case defect detection system in other languages. Lexical database is needed as a reference for the system to recognize the processed text. Requirement writing template is also adapted to prevent complex writing of sentence structure. Those research results are the foundation for this research to develop a use case scenario examiner case tool in Indonesian. This case tool can manage use case scenario into a project, and examine those scenarios. Testing results on all aspects of the system are valid with a percentage of 100%, therefore therefore this system is feasible to use as a case tool to simiplify the use case scenario defect detection process.